MICOPLASMOSE FELINA - RELATO DE CASO - Paetzold, Sandy Munique Piper; Socolhoski, Brenda Viviane Götz; Marasca, Isabela Alegranzi; Beck, Cristiane; Silva, Tanara Raquel De Oliveira Da (Salão do Conhecimento, 2019)
Relato de caso acompanhado no Hospital Veterinário da UNIJUÍ